Controle de vibração em pás de rotor de helicóptero com pitch link superelástico de LMF NiTi - Oliveira, Andersson Guimarães (2022)
Vibration problems in helicopters are a concern of manufacturers and users in the aeronautical industry. This issue represents a challenge, mainly in the vibration control and dynamic characterization because the vibration measurements are difficult to perform, especially on helicopter rotating parts. With smart materials, the industry seeks solutions that contribute to vibration reduction without generate a negative impact on weight and system complexity. This study design, produce and test a Shape Memory Alloy (SMA) device that replace the original pitch link of a helicopter rotor prototype in order to vibration reducing in the critical frequency employing hysteretic passive damping, without energy machine consumption. The study employs an indoor two-bladed helicopter prototype to perform the critical operation frequency identification in the original mechanism to stablish a reference condition. In sequence, the designed SMA pitch link device replaces the original pitch link in order to perform a comparative analysis of the dynamic response. After a battery of tests, in long-term experiments with closed and distalizing springs, the results demonstrate that the device exhibited the best response when employing closed springs. The results with the SMA device demonstrate a reduction in amplitudes vibration of about 2dB, reaching about 4dB in severe test conditions. In operational circumstances, this attenuation represents crew comfort increasing, performance improvement, and wear reduction of mechanical systems due to vibration.